Performance of Bidirectional Converter Based On Grid Application - D. Vidhyalakshmi; K. Balaji (Institute of Advanced Engineering and Science, 2018)
A transformer less bidirectional inverter fed grid-connected system has implemented and function as both forward and reverse power flow by battery and photovoltaic system. In dc distributed system has utilized the renewable energy such as PV, wind, battery and fuel system. In conventional method the dc bus regulation by using the one line cycle regulation method and one-sixth line cycle regulation. In proposed method utilize both converter and inverter operates bidirectional direction and utilize both solar and PV source. The solar energy had less cost, pollution less energy generation and fed into the bidirectional converter. The PI-based control method is used to operate both forward and reverse direction. The model predictive control method is used in the bidirectional inverter for control the current and voltage of the grid-connected system. The power flow control in the distribution system by the constant power loads such as dc/dc converter because conduct the negative dynamic impedance. The three-phase bidirectional inverter is designed and implemented in MATLAB/Simulink environment.